Integrated Solar Photovoltaic And Thermal Collector System For Enhanced Energy Efficiency - Sameera Aijaz, Pabitra Kumar Nayak, Dharminder Kumar (International Journal of Advanced Science and Technology, 2020)
In India, the development of renewable sources of energy like as wind, hydro and solar energy has been increasing.. The combination of a photovoltaic and thermal collector design, called a hybrid photovoltaic and thermal (PV/T) system, was known to be simultaneously converting power energy to electricity.This system has been achieved to overcome the less energy efficiency found by using separate solar power technologies to improve energy output and permit better use of solar energy. The concept of make use of  a hybrid photovoltaic and heat collection system is therefore to maximize and increase  the output  performance of the PV panels by using the necessary technology to incorporate conversion hot water or room heating thermal energy for residential or industrial uses.The two solar technologies are combined, as the performance of photovoltaic cells decreases with increasing unit temperature.